Prevention of mother-to-child transmission of HIV infection: Views and perceptions about swallowing nevirapine in rural Lilongwe, Malawi - Nyirenda Lot J; O'Gorman Deirdre A; Theobald Sally J (BMC, 2010)
Abstract Background In 2006 the World Health Organization described the status of prevention of mother to child transmission (PMTCT) service implementation as unacceptable, with an urgent need for a renewed public health approach to improve access. For PMTCT to be effective it needs to be accessible, acceptable and affordable; however research in Africa into accessibility, uptake and acceptability of PMTCT services has been predominately urban based and usually focusing on women who deliver in hospitals. The importance of involving other community members to strengthen both PMTCT uptake and adherence, and to support women emotionally, has been advocated. Urban men's and rural traditional birth attendants' (TBAs) involvement have improved uptake of HIV testing and of nevirapine. Methods A qualitative study was carried out in a rural district of Malawi's central region to explore the views about and perceptions of PMTCT antiretroviral treatment. Semi-structured interviews and focus group discussions were held with antenatal and postnatal women, fathers, grandmothers, TBAs, community leaders and PMTCT health workers. Results Two broad themes of findings emerged: those that relate to the hospital PMTCT service, and those that relate to the community. Trust in the hospital was strong, but distance, transport costs and perceived harsh, threatening health worker attitudes were barriers to access. Grandmothers were perceived to have influence on the management of labour, unlike fathers, but both were suggested as key people to ensure that babies are brought to the hospital for nevirapine syrup. TBAs were seen as powerful, local, and important community members, but some as uneducated. Conclusion PMTCT was seen as a community issue in which more than the mother alone can be involved. To support access to PMTCT, especially for rural women, there is need for further innovation and implementation research on involving TBAs in some aspects of PMTCT services, and in negotiating with women which community members, if any, they would like to support them in ensuring that newborn babies receive nevirapine.